Numerical investigation of dynamic installation of torpedo anchors in clay. (1st November 2015) - Kim, Y.H.; Hossain, M.S.; Wang, D.; Randolph, M.F.
Abstract: This paper reports the results from three-dimensional dynamic finite element analysis undertaken to provide insight into the behaviour of torpedo anchors during dynamic installation in non-homogeneous clay. The large deformation finite element (LDFE) analyses were carried out using the coupled Eulerian–Lagrangian approach, modifying the simple elastic-perfectly plastic Tresca soil model to allow strain softening, and incorporate strain-rate dependency of the shear strength using the Herschel–Bulkley model. The results were validated against field data and centrifuge test data prior to undertaking a detailed parametric study, exploring the relevant range of parameters in terms of anchor shaft length and diameter; number, width and length of fins; impact velocity and soil strength. The anchor velocity profile during penetration in clay showed that the dynamic installation process consisted of two stages: (a) in Stage 1, the soil resistance was less than the submerged weight of the anchor and hence the anchor accelerated; (b) in Stage 2, at greater penetration, frictional and end bearing resistance dominated and the anchor decelerated. The corresponding soil failure patterns revealed two interesting aspects including (a) mobilization of an end bearing mechanism at the base of the anchor shaft and fins and (b) formation of a cavity above the shaft of the installing anchor and subsequent soil backflow into the cavity depending on the soil undrained shear strength. To predict the embedment depth in the field, an improved rational analytical embedment model, based on strain rate dependent shearing resistance and fluid mechanics drag resistance, was proposed, with the LDFE data used to calibrate the model. Highlights: Anchor embedment depth= f (impact velocity, anchor geometric parameters). Anchor embedment depth= f (soil shear strength). Anchor velocity profile consisted of two stages. Soil failure patterns (a) end bearing mechanism and (b) cavity and soil backflow. For assessing embedment depth of torpedo anchors, two models were proposed.